Стационарные и переходные процессы в электромеханической системе нанесения полимерной изоляции на жилу сверхвысоковольтных кабелей - Щерба, А.А.; Подольцев, А.Д.; Золотарев, В.М. (Технічна електродинаміка, 2012)
The stationary and transient processes in the system of variable-frequency asynchronous drives, controlling the motion parameters of metal cable conductor with polymer insulation in the inclined vulcanization chamber are studied. The analytical expressions for matching the required tension of free sagging metal conductor with camera parameters are determined. It has been created the Simulink-model for regulation of transient electrical and mechanical processes, such as vibration of moving conductor in the transverse and longitudinal directions taking into account the changes of the conductor parameters, retarding forces and supply voltage.